Efeitos cardiovasculares e renais da denervação seletiva das fibras sensoriais renais na Hipertensão Renovascular Experimental - Lopes, Nathalia Rodrigues [UNIFESP] (2019)
It is known that oxidative stress and increased renal sympathetic nervous activity (rSNA) play an important role in arterial hypertension (AH). Under physiological conditions, renal sympathetic fibers control renin release, sodium reabsorption, and renal vasoconstriction. In addition to innervation of the sympathetic nervous system (SNS), the kidney is innervated by sensory or afferent fibers, which signal intrarenal changes to the brain and, through neurohumoral pathways, can modify the rSNA. In AH, studies have shown that the renal nerve contributes to the development of injury, inflammation and increased renal excretion of proteins. Although clinical studies have shown that renal denervation is an effective method of reducing blood pressure (BP) in hypertensive patients refractory to pharmacological treatment, the removal of renal sympathetic fibers may compromise the physiological role of SNS in renal BP control of homeostatic challenges. Therefore, in light of these evidences, this work evaluated the effects of selective denervation of renal sensory fibers on cardiovascular and renal parameters of Wistar rats 2 kidneys, 1 clip (2K1C). For the induction of AH, the left renal artery was partially occluded by the insertion of a silver clip (0.2 mm gap). After 4 weeks, afferent renal denervation (ARD) was performed by exposing the renal nerve to a 33 mM capsaicin solution for 15 minutes, it is known that capsaicin at high concentrations is able to desensitize the transient potential vanilloid receptor 1 (TRVP1) and deplete the production of substance P and the calcitonin peptide-related gene (CGRP). After 2 weeks of ARD, there was a significant reduction of mean arterial pressure (MAP) and rSNA for both ischemic and contralateral kidneys. As for oxidative stress, a reduction in both kidneys was observed, ischemic and contralateral in the 2K1C group. In addition, there was an increase in the expression of Ang II AT-1 receptors and the subunits of NADPH oxidase, p47phox and gp91phox in the ischemic kidney of hypertensive animals and ARD was able to reduce these levels. Also, ARD was able to improve proteinuria and microalbuminuria, without alteration in the excretion of low molecular weight proteins, such as RBP4 in hypertensive rats. However, in relation to the evaluation of the expression of the structural proteins of the podocytes, podocin and nephrine, and of the endocytic receptors present in the renal tubule, megalin and cubilin, no differences were found between groups in both kidneys. Taken together, our data demonstrate that although ARD partially reduces BP, rSNA, renal oxidative stress, proteinuria, and glomerular damage are significantly improved in the renovascular model. Therefore, the present study suggests that the removal of renal afferent fibers is an effective method in improving AH and sympathetic hyperactivity in a model of experimental hypertension.